Photoactivation of silicon rhodamines via a light-induced protonation - Frei, Michelle S.; Hoess, Philipp; Lampe, Marko; Nijmeijer, Bianca; Kueblbeck, Moritz; Ellenberg, Jan; Wadepohl, Hubert; Ries, Jonas; Pitsch, Stefan; Reymond, Luc; Johnsson, Kai (Nature Communications, 2019)
Activatable fluorophores are of interest for a wide range of applications but the need for caging groups complicates their development and application. Here, the authors report on a photoactivatable silicon rhodamine derivative and its application in live cell imaging and single-particle tracking.